Outbreak of mirid bugs (Heteroptera: Miridae) on hops - Josef Šedivý; Vladimír Řehák (Plant Protection Science, 2000)
Outbreaks of mirid-bugs on hop in Czech hop region recurred in 1875, I 928/29, 1947/48 and 1998/99. The spectrum and importance of specific harmful mirid species varied with the type of hop-garden. Calocoris fulvomaculatus was a dominant species in pole hop-gardens. Lygus rugulipennis was a dominant pest in trellises in 1998/99, when it locally damaged more than 50% of bines. Mirid-bugs migrate to hops at temperatures over l0°C, and stay there over the growing season. Bine tops are damaged by sucking, drying back later. Bines that grow from under the sites of injury are distorted and cease twining. This damage is caused before and after the training, up to 2.5 m of the bines height. An economic threshold is at I0% of damaged bine tops and more in the period after training. Years with warm, dry autumn, mild winter and warm, dry spring provide favourable conditions for outbreaks of the mirid-bugs and their spring activities.